2010
DOI: 10.1159/000312127
|View full text |Cite
|
Sign up to set email alerts
|

Serum Eosinophil Cationic Protein and 27 Cytokines/Chemokines in Acute Exacerbation of Childhood Asthma

Abstract: Background: Little information is available on eosinophil activation and cytokine/chemokine responses in childhood asthma, thus we examined serum eosinophil cationic protein (ECP) and 27 types of cytokines/chemokines in acute exacerbation of asthma (acute asthma) and stable asthma. Methods: We determined peripheral eosinophil count, and the serum levels of ECP and 27 types of cytokines/chemokines (IL-1β, IL-1ra, IL-2, -4, -5, -6, -7, -8, -9, -10, -12, -13, -15 and -17, IFN-γ, IP-10, TNF-α, GM-CSF, G-CSF, MCP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 49 publications
(32 reference statements)
6
38
2
Order By: Relevance
“…On the other hand, oral glucocorticoids improve lung function and decrease the elevation of serum IL-6, soluble ICAM-1, and ECP [31]. Recently, we reported that treatment that included systemic corticosteroids could decrease serum levels of ECP, IL-5, IL-6, IL-1ra, and IP-10 in acute exacerbation of childhood asthma [32]. In this study, we further found that treatment with systemic corticosteroids decreased serum ECP and IL-5 in rhinovirus-induced acute exacerbation of asthma but not in RS virus-induced acute exacerbation of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, oral glucocorticoids improve lung function and decrease the elevation of serum IL-6, soluble ICAM-1, and ECP [31]. Recently, we reported that treatment that included systemic corticosteroids could decrease serum levels of ECP, IL-5, IL-6, IL-1ra, and IP-10 in acute exacerbation of childhood asthma [32]. In this study, we further found that treatment with systemic corticosteroids decreased serum ECP and IL-5 in rhinovirus-induced acute exacerbation of asthma but not in RS virus-induced acute exacerbation of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…bronchoalveolar lavage (BAL) or induced sputum [6][7][8][9]. The measurement of cytokine levels in serum may be a valuable alternative, as standardized collection of peripheral blood is practical among participants of all ages for large epidemiological studies and for routine clinical practice [10,11]. Furthermore, multidimensional approaches for data analysis may allow the identification of pools of cytokines with diagnostic performance superior to single cytokines in terms of sensitivity, specificity and robustness [12].…”
Section: Introductionmentioning
confidence: 99%
“…ECP has been as so cia ted wi th se ve ral pat ho lo gic condi tio ns. The lar ge st num ber of cli ni cal stu dies deal wi th ato pic di sea ses: as thma, al ler gic rhi ni tis, atopic eczema/dermatitis syndro me (AEDS) (53)(54)(55)(56). Ele va ted se rum va lues are pro por tio nal to the inten si ty of al ler gic in fl am ma tion and in di ca te acu te al ler gen expo su re.…”
Section: Ni Cal Sig Ni Fi Can Ce Of Ecpmentioning
confidence: 99%
“…Howe ver, as ECP con cen tra tion in tis sue and bo dy fl ui ds cor re la tes wi th di sea se ac ti vi ty, ECP may aid in as ses si ng the se ve ri ty of as thma and in reac hi ng a de ci sion on the ra py type and in ten si ty (54,55), par ti cu lar ly in chil dren be cau se of freque nt dis crepan cy be tween physi cia n's as ses sme nt and the chil d's sub jec ti ve expe rien ce of di sea se. By fol lowing-up chan ges in the ECP le vel af ter in tro duc tion of the ra py, it is pos sib le to mo ni tor effi cien cy of a spe ci fi c drug do se and to cor re ct do sa ge to avoid over do si ng or as thma at ta ck be cau se of a too low…”
Section: Ecp and As Thmamentioning
confidence: 99%
See 1 more Smart Citation